Inter-Industry Risk-Returns Heterogeneity: A Market Model Approach - Nainggolan, Rexon; Morada, Rhody Laynn K. (Penerbit Goodwood, 2026)
Purpose: This study challenges the assumption in financial theory that industry grouping is a robust descriptor of firms’ risk-return profile by providing evidence of their heterogeneity. Research Methodology: The study uses the market model and several robust statistical tests to assess the heterogeneity of the sector and firm-level risk-return profiles, including the Coefficient of Variance, the Shapiro-Wilk Test for Data Normality, the Kruskal-Wallis H test, and Levene's Test. Results: The study finds significant heterogeneity in Alpha across sectors and industries. On the other hand, systematic risk exposure, as measured by Beta, exhibits substantial sectoral commonality. However, while firm performance varies across sectors, market sensitivities remain similar across sectors, suggesting that systematic risk primarily reflects individual firms. Conclusions: The results contradict the traditional view of the high-risk-high-return paradigm, suggesting that firms with higher returns do not necessarily inherit higher risk. Thus, the results strongly support the resource-based view over the structure-conduct-performance framework, as intra-industry differences exceed inter-industry differences. Limitations: The study focuses on alpha and beta parameters as measures of risk-return profiles and does not cover other external factors, such as macroeconomic or geopolitical factors. Contributions: By decomposing this spread into its components, the study provides heterogeneity indices that can be used to measure firms’ risk-returns profiles from the perspective of alpha and beta coefficients.